Learning electronics project inside a control inspired conceptual map - Garrido, Paulo (2015)
This paper describes two laboratory and project semester modules in the Electronics Engineering programme of Universidade do Minho. Along time, the learning objectives of these modules evolved from integrating conventional laboratory work across disciplines to include first time experience in project of electronics with collaboration of industry. The design of the modules joins elements of conventional laboratory work, project based learning and cooperation with industry. Cooperation with industry has a crucial role in framing the project work and ultimately the laboratory work. Control is, beyond one of the topics to be learned, a main source of inspiration for the design of the modules at large, as the feedback loop concept is used to unify laboratory work from several disciplines with project into a coherent learning experiment.